ACCELERATING RENEWABLE ENERGY DEVELOPMENT TOWARD ENERGY SECURITY - Aditya Arso Perdana; Muhammad Ery Wijaya; Ichsan Ichsan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The need for electricity in Indonesia increases daily, including in the North Halmahera district. Using primary energy sources, which are still dominated by fossil fuels, will later affect national energy security sustainability. The new and renewable energy can be a solution for North Halmahera to overcome energy security problems and reduce its emission level. The North Halmahera Government seeks to utilize renewable energy sources to increase energy security by looking at energy availability, affordability, and sustainability. Therefore, this study aims to provide strategies or recommendations to accelerate renewable energy development in North Halmahera so that energy security and environmental sustainability in North Halmahera are maintained. Data will be collected from review of various literatures and government documents. Based on the RUED and the RUPTL, the North Halmahera Government can formulate and determine plans to accelerate the fulfillment of regional energy security by increasing energy availability, affordability, and sustainability. The North Halmahera Government can make more efficient regional regulations and not be burdensome to various parties. Regional regulations must provide security for investors, developers, and buyers of renewable energy products.